2016
DOI: 10.21608/asejaiqjsae.2016.2535
|View full text |Cite
|
Sign up to set email alerts
|

Treated Wastewater Irrigation Promotes the Growth and Nodulation of Acacia Species

Abstract: The scarcity of irrigation water is one of the vital factors limiting crop production in arid countries. The critical shortage of water necessitates the development of new water sources, and the use of wastewater is considered one of the best solutions for solving this water scarcity. An experiment was conducted to investigate the effect of primary treated wastewater irrigation on growth parameters, nodulation, macro and micronutrients for Acacia ampliceps (Maslin.) and Acacia origena (Hunde.) seedlings grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Guidelines for the safe use of treated wastewater (TWW)) were published by World Health Organization (WHO, 2006). Elbana et al (2014) and Shetta (2016) showed that use of treated wastewater provides a reliable alternative source for irrigation in arid and semi-arid regions. studies as (Qadir and Aziz, 2021;Aboamera et al, 2017;Ismail et al, 2013;Rashad et al, 2012), explained that the CP ranged from 12.24 to 80.61% by using treated wastewater and different outlets types with flow rate ranged from 1.6 to 8 L/h after181operating hours.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for the safe use of treated wastewater (TWW)) were published by World Health Organization (WHO, 2006). Elbana et al (2014) and Shetta (2016) showed that use of treated wastewater provides a reliable alternative source for irrigation in arid and semi-arid regions. studies as (Qadir and Aziz, 2021;Aboamera et al, 2017;Ismail et al, 2013;Rashad et al, 2012), explained that the CP ranged from 12.24 to 80.61% by using treated wastewater and different outlets types with flow rate ranged from 1.6 to 8 L/h after181operating hours.…”
Section: Introductionmentioning
confidence: 99%